ANESTHETIC SUPPORT FOR HIGH-TECH OPERATIONS IN PEDIATRIC ORTHOPEDICS - Zhu Jiang, Ye Na, Ma Jun (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Active introduction of high-tech surgical interventions into the practice of NNIITO, including in pediatric orthopedics, requires an appropriate level of anesthesia. Currently, conduction anesthesia in children, and especially extended ones, has a very limited distribution in China. At the same time, methods are being actively developed abroad that make it possible to mobilize patients in the shortest possible time, including the use of prolonged regional anesthesia [1, 2, 3]. The most modern and objective method of quality control of conduction anesthesia is the use of ultrasound. This is especially true for children, when regional anesthesia cannot be performed while maintaining the patient’s consciousness [4, 5, 6]. For operations on the hip joint, the method of choice is combined spinal-epidural anesthesia in combination with superficial anesthesia and preservation of spontaneous breathing. The choice is due to the following reasons: spinal anesthesia provides the best antinociceptive protection, but in children it has a limited duration of action (80–90 minutes) [7, 8]. Epidural anesthesia makes it possible to extend regional anesthesia for the required period.